2021
DOI: 10.1111/aogs.14204
|View full text |Cite
|
Sign up to set email alerts
|

Placental characteristics in different types of selective fetal growth restriction in monochorionic diamniotic twins

Abstract: Introduction This study aimed to explore the differences in placental characteristics among three types of selective fetal growth restriction (sFGR) in monochorionic diamniotic twin pregnancies. Material and methods A total of 123 placentas with sFGR between April 2013 and October 2019 were retrospectively analyzed after dye injection. Placental characteristics were compared among the three types. Results The gestational age at diagnosis and delivery was less in sFGR II and III than in sFGR I (22.9 [21.7–33.6]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Its dynamic nature hampers the determination of a “definitive” Gratacós type. At present, available studies base the classification of a pregnancy complicated by sFGR on either a single observation of abnormal UA Doppler flow patterns, the final UA Doppler flow pattern prior to delivery or the most prevalent Doppler flow pattern 17,24,26 . Therefore, the classification of sFGR according to Gratacós is still not uniformly applied in literature, leading to substantial incomparability between studies with regards to outcome per sFGR type.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Its dynamic nature hampers the determination of a “definitive” Gratacós type. At present, available studies base the classification of a pregnancy complicated by sFGR on either a single observation of abnormal UA Doppler flow patterns, the final UA Doppler flow pattern prior to delivery or the most prevalent Doppler flow pattern 17,24,26 . Therefore, the classification of sFGR according to Gratacós is still not uniformly applied in literature, leading to substantial incomparability between studies with regards to outcome per sFGR type.…”
Section: Discussionmentioning
confidence: 99%
“…At present, available studies base the classification of a pregnancy complicated by sFGR on either a single observation of abnormal UA Doppler flow patterns, the final UA Doppler flow pattern prior to delivery or the most prevalent Doppler flow pattern. 17,24,26 Therefore, the classification of sFGR according to Gratacós is still not uniformly applied in literature, leading to substantial incomparability between studies with regards to outcome per sFGR type. It was recently suggested that a modification of the Gratacós classification is necessary that includes GA at diagnosis, variation in UA Doppler flow patterns, ductus venosus Doppler (has been shown to be a powerful prognostic marker for sFGR and might identify infants with increased risk for neonatal mortality and morbidity 27 ) and the co-existence of TTTS.…”
Section: Interpretation Of the Findingsmentioning
confidence: 99%
See 2 more Smart Citations